KARAKTERISTIK GOOD CORPORATE GOVERNANCE PADA BANK SYARIAH DAN BANK KONVENSIONAL - Aldira Maradita (Universitas Airlangga, 2014)
Basically, good corporate governance is the implementation of the vision and mission of Islamic banking. The main point is the reference of this visionis to fulfil the principle of prudence (prudential banking). Meanwhile, point mission is to prepare and implement the concept of risk-based regulation and supervision to ensure the sustainability of Islamic banking operations in accordance with the characteristics that Islamic corporate governance meant that economic activity actually undertake into achieve its goal, both goals hablumminallah and hablumminannas. This is reasonable, because Islamic Corporate Governance has become the soul of all parties involved in the company (stakeholders), the fraud, speculation, insider-trading, or else can be minimized.Keywords: GCG, sharia banking, conventional banking.